Climate Litigation in Times of Upheaval: Media Framing of Responsibility and Guilt in the Climate Crisis (PROKLA. Journal of Critical Social Science, 2025)
Climate litigation has become an important instrument of the climate movement. The frame analysis in this article shows that climate litigation can contribute to the legitimization of climate policy demands by assigning responsibility for climate protection to state actors and companies. They also show a certain robustness against discursive devaluation, which is supported by antagonistic framing. Limits of positive reporting can be seen in proceedings against the automotive industry.
Keywords: Climate Justice; Climate Movement; Framing; Media; Socio-Ecological Transformation